2016
DOI: 10.1007/s13193-015-0485-x
|View full text |Cite
|
Sign up to set email alerts
|

Totally Implantable Venous Access Devices in Children Requiring Long-Term Chemotherapy: Analysis of Outcome in 122 Children from a Single Institution.

Abstract: Children with malignancy require venous access that is reliable, safe and compliant on a long-term basis. There is little data available on utilization of totally implantable venous access devices (TIVAD) for long term chemotherapy in children in an Indian setting [1]. We report our long-term follow-up results of utilization of totally implantable venous access devices for long-term chemotherapy in children. This was a retrospective analysis of 122 children requiring longterm chemotherapy done between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
(27 reference statements)
3
19
4
Order By: Relevance
“…Acute leukemias combined with lymphomas constituted 69% of our study group (Table 1), which is similar to the incidence reported in most of the studies published [79]. This is because leukemia is the most common pediatric malignancy, constituting 25% of cases [10].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Acute leukemias combined with lymphomas constituted 69% of our study group (Table 1), which is similar to the incidence reported in most of the studies published [79]. This is because leukemia is the most common pediatric malignancy, constituting 25% of cases [10].…”
Section: Discussionsupporting
confidence: 85%
“…The IJV was the preferred vein in most of the studies including ours [1,3,7,9,11]. The advantages of the IJV over the SCV are that it is associated with lower incidence rates of pneumothorax, upper extremity deep vein thrombosis, chylothorax, catheter pinch-off, and no brachial plexus injury [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TIVADs are commonly used in adults and pediatric patients for the administration of chemotherapy, antibiotics, or parenteral nutrition. The use of these devices has improved the compliance of pediatric patients [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%